Hydrate-Based Methane Storage in Biodegradable Hydrogels Absorbing Dilute Sodium P-Styrenesulfonate Solution - Fangzheng Hua; Kang Tan; Jingyu Lv; Fei Wang; Mengting Sun (Gels)
Developing an exceptional reaction medium with high promotion efficiency, desirable biodegradability and good recyclability is necessary for hydrate-based methane storage. In this work, a kind of eco-friendly hydrogel, polyvinyl alcohol-co-acrylic acid (PVA-co-PAA), was utilized to absorb dilute sodium p-styrenesulfonate (SS) solution, for constructing a hybrid reaction medium for methane hydrate formation. Hydrogels or dilute SS solutions (1–4 mmol L−1) had weak or even no promoting effects on hydrate formation kinetics, while the combination of them could synergistically promote methane hydrate formation. In hydrogel-SS hybrid media containing 1, 2, 3 and 4 mmol L−1 of SS solutions, the storage capacity reached 121.2 ± 1.6, 121.5 ± 3.1, 122.6 ± 1.9 and 120.6 ± 1.6 v/v, respectively. In this binary reaction system, the large surface area of hydrogels provided hydrate formation with sufficient nucleation sites and an enlarged gas–liquid interface, and in the meantime, the dilute SS solution produced an adequate capillary effect, which together enhanced mass transfer and accelerated hydrate formation kinetics. Additionally, the hybrid medium could relieve wall-climbing hydrate growth and improve poor hydrate compactness resulting from the bulk SS promoter. Moreover, the hybrid medium exhibited a preferable recyclability and could be reused at least 10 times. Therefore, the hydrogel-SS hybrid medium can serve as an effective and eco-friendly packing medium for methane hydrate storage tanks, which holds great application potential in hydrate-based methane storage technology.